Service Orientation in Holonic and Multi-Agent Manufacturing and Robotics - Borangiu, Theodor; Trentesaux, Damien; Thomas, Andre (Studies in Computational Intelligence, 2014)
This volume gathers the peer reviewed papers which were presented at the third edition of the International Workshop "Service Orientation in Holonic and Multi-agent Manufacturing and Robotics - SOHOMA'13" organized on June 20-22, 2013 by the Centre of Research in Computer Integrated Manufacturing and Robotics - CIMR Bucharest, and hosted by the University of Valenciennes, France. The book is structured in five parts, each one covering a specific research domain which represents a trend for modern manufacturing control: Distributed Intelligence for Sustainable Manufacturing, Holonic and Multi-Agent Technologies for Manufacturing Planning and Control; Service Orientation in Manufacturing Management and Control, Intelligent Products and Product-driven Automation and Robotics for Manufacturing and Services. These five evolution lines have in common concepts related to service orientation in a distributed planning and control agent-based industrial environment; today it is generally recognized that the Service Oriented Enterprise Architecture paradigm has been looked upon as a suitable and effective approach for industrial automation and management of manufacturing enterprises.    .